2020
DOI: 10.1002/er.5491
|View full text |Cite
|
Sign up to set email alerts
|

A game theoretic analysis of a closed‐loop water‐energy nexus: The effect of technology efficiency and market competition on the market equilibrium and social welfare

Abstract: Water and energy are two scarce and concerning resources interconnected in the closed-loop water-energy nexus, exemplifying the co-dependence of water and energy production. In this article, we investigate the interaction between the industries of these two resources and model it as a simultaneous game. We consider a supply chain that consists of water suppliers (WSs), power suppliers (PSs), and consumers of these commodities. In the supply chain, WSs purchase power from the power market, and PSs purchase wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Systems dynamic (SD) modeling is applied in Reference 27 on a watershed scale to holistically understand the W‐EN, demonstrating that there are critical synergies of water and energy and compensation at the Massachusetts Water Resources Authority (MWRA) that enable the integration of water and energy management to achieve better results. The interaction between the water and energy industries is investigated in Reference 31, being modeled as a simultaneous game.…”
Section: State Of the Artmentioning
confidence: 99%
“…Systems dynamic (SD) modeling is applied in Reference 27 on a watershed scale to holistically understand the W‐EN, demonstrating that there are critical synergies of water and energy and compensation at the Massachusetts Water Resources Authority (MWRA) that enable the integration of water and energy management to achieve better results. The interaction between the water and energy industries is investigated in Reference 31, being modeled as a simultaneous game.…”
Section: State Of the Artmentioning
confidence: 99%
“…Li et al [40] investigated the dynamic model's global dynamic behavior with consumer surplus and found that chaos may lead to the reduction of social welfare. More related studies can be found in references [41]- [44].…”
Section: Introductionmentioning
confidence: 99%